Reliable genetic diagnosis of NCF1 (p47phox)-deficient chronic granulomatous disease using high-throughput sequencing - Hsu, Amy P.; Karlins, Eric; Lack, Justin; Pepper, T. Joseph; Lau, Karen; Marshall-Batty, Kimberly R.; Long Priel, Debra; Davis, Joie; Fink, Danielle L.; Zerbe, Christa S.; Gallin, John I.; Malech, Harry L.; et al. (Frontiers in Immunology, 2025)
IntroductionChronic granulomatous disease is caused by mutations in any of the 6 components of the phagocytic NADPH oxidase complex including gp91phox, p47phox, p22phox, p40phox, p67phox, or EROS. Functional assays include reactive oxygen species (ROS) production, flow cytometry, and immunoblotting for NADPH proteins. The advent of high-throughput sequencing allows genetic diagnosis for all components except NCF1 (p47phox) due to two, nearly identical, pseudogenes (NCF1B, NCF1C). The majority of NCF1-CGD patients carry a 2-base deletion caused by crossover between NCF1 and NCF1B or NCF1C. Currently, NCF1 deficiency is diagnosed functionally: a characteristic DHR with low levels of residual ROS, loss of p47phox on immunoblot, or digital droplet PCR or Gene-scan to enumerate intact (GTGT) or deleted (ΔGT). While this provides patients a clinical CGD diagnosis, for the 20% of NCF1-CGD patients with a non-ΔGT mutation a definitive genetic diagnosis is still lacking.MethodsWe developed a bioinformatic method using existing short or long-read sequencing data from 48 NCF1-CGD patients or carriers.ResultsWe identified both ΔGT and non-ΔGT NCF1 gene mutations. Additionally, we confirm that the presence of ΔGT in NCF1 is due to pseudogene copy into the NCF1 locus. We compare NCF1 sequence from NCF1-CGD patients to cohorts of non-NCF1-CGD and healthy controls (1000Genomes), demonstrating pseudogene replacement of NCF1 in NCF1-CGD as well as the reciprocal replacement of NCF1B or NCF1C by NCF1 in some healthy controls.DiscussionWith this method, reanalysis of existing sequence data may provide genetic diagnosis to NCF1-CGD patients. This technique may be modified for other diagnostically relevant pseudogenes.